Determinant Factors of Low Birth Weight in Infants - Wahyu Gito Putro Putro; Putri Septiani Azzahra Pranoto; Lela Kania Rahsa Puji; Kadek Darmawan (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2025)
Low Birth Weight (LBW) is a significant public health issue as it contributes to morbidity and mortality rates in neonates, infants, and children. Although many studies have examined the risk factors for LBW, no research has yet explored LBW cases in South Tangerang. This study aims to identify the determinant factors affecting LBW incidence in South Tangerang. This research employed a descriptive-analytic design with cross-sectional approach conducted at South Tangerang Hospital from October 2022 to January 2023. The study population consisted of 130 LBW cases, and sample of 97 respondents was randomly selected using Lameshow (5%). Data were collected through interviews using a validated and reliable questionnaire. Data analysis was performed using univariate and bivariate analysis with the Chi-square test, and Fisher’s Exact Test was used as an alternative when expected values were not met. The significance level was set at p-value <0.05. The results showed no significant relationship between maternal age (p=0.655), parity (p=1.000), gestational age (p=1.000), birth spacing (p=0.118), or chronic illness (p=0.152) and LBW incidence. Although no significant associations were found, further research is needed. These findings can serve as a foundation for more targeted intervention programs in maternal and child healthcare to prevent and address LBW.